2018
DOI: 10.24167/celt.v18i1.555
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Herringbone Technique in Reading Comprehension at Second Semester of Non-English Department

Abstract: Herringbone technique is the technique to help students find important information and main idea in a text by seeking the answer of six comprehension questions on a diagram. This study is intended to know how the lecturer’s implement herringbone technique to the students’ reading comprehension, especially detail information and main idea. The research was done at STAI Bahrul ‘Ulum Tambakberas. The subject of the study was the second semester of PAI-A students consisting 33 students. The study is descriptive qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Two students are unable to answer the questions asked by the teacher due to lack of understanding of the material presented, even most students only open their respective handbooks when given questions. Three learning is still centered on the Teacher (teacher center) so that all students' understanding is only linked to the understanding that teachers and students tend to be less active (Rohmah, 2018). Likewise with PAI learning that students should be enthusiastic and enthusiastic in following it but, it is not so.…”
Section: Introductionmentioning
confidence: 99%
“…Two students are unable to answer the questions asked by the teacher due to lack of understanding of the material presented, even most students only open their respective handbooks when given questions. Three learning is still centered on the Teacher (teacher center) so that all students' understanding is only linked to the understanding that teachers and students tend to be less active (Rohmah, 2018). Likewise with PAI learning that students should be enthusiastic and enthusiastic in following it but, it is not so.…”
Section: Introductionmentioning
confidence: 99%
“…Various experts have given their best definitions of reading. Summing up, reading could be defined as the interaction between reader and writer with the reading texts as the medium (Eviyuliwati & Sarwan, 2018;Iftanti, 2012;Rohmah, 2018) . From this point of view, it could be concluded that reading should have at least three elements; reader, writer, and reading text.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehending the messages is the key to reading. There is no reading without comprehension (Eviyuliwati & Sarwan, 2018;Rohmah, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In secondary schools, reading is the most crucial skill for foreign language students because they have little exposure to English outside their class, and mostly the information in English comes from reading (Ambarini et al, 2018). Furthermore, reading doesn't merely orient to know the meaning of words or recognize the vocabulary in English texts but comprehend the content of information or message implicitly and explicitly from the texts as well (Rohmah, 2018).…”
Section: Introductionmentioning
confidence: 99%